2022
DOI: 10.3389/fnhum.2022.811547
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Investigation of Sensory Processing in Autism: Parent- and Self-Report Questionnaires, Psychophysical Thresholds, and Event-Related Potentials in the Auditory and Somatosensory Modalities

Abstract: BackgroundReconciling results obtained using different types of sensory measures is a challenge for autism sensory research. The present study used questionnaire, psychophysical, and neurophysiological measures to characterize autistic sensory processing in different measurement modalities.MethodsParticipants were 46 autistic and 21 typically developing 11- to 14-year-olds. Participants and their caregivers completed questionnaires regarding sensory experiences and behaviors. Auditory and somatosensory event-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…Personalized interventions that seek to assess an autistic child's speci c pattern of sensory reactivity differences and ameliorate challenges associated with each domain could also be assessed within this framework, using modality-speci c assessments of each sensory response pattern to monitor the effectiveness of each putative "active ingredient" of the intervention. A shift in measurement practices will also allow researchers to associate these single-modality behavioral subconstructs with psychophysical and/or neurophysiological measures within a given modality (e.g., 74,75), informing theories of the neurocognitive underpinnings of certain types of sensory reactivity in autism (e.g., 39,149,150). Though we do not claim a single-modality perspective to be advantageous in all cases or for all research questions (particularly for those focused on "real-world" multisensory contexts), we believe that a greater diversity of theoretical approaches and frameworks within sensory autism research is needed to make optimal progress towards improving the lives of autistic people within this line of work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Personalized interventions that seek to assess an autistic child's speci c pattern of sensory reactivity differences and ameliorate challenges associated with each domain could also be assessed within this framework, using modality-speci c assessments of each sensory response pattern to monitor the effectiveness of each putative "active ingredient" of the intervention. A shift in measurement practices will also allow researchers to associate these single-modality behavioral subconstructs with psychophysical and/or neurophysiological measures within a given modality (e.g., 74,75), informing theories of the neurocognitive underpinnings of certain types of sensory reactivity in autism (e.g., 39,149,150). Though we do not claim a single-modality perspective to be advantageous in all cases or for all research questions (particularly for those focused on "real-world" multisensory contexts), we believe that a greater diversity of theoretical approaches and frameworks within sensory autism research is needed to make optimal progress towards improving the lives of autistic people within this line of work.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the most appropriate "level of analysis" (supra-modal versus modality-speci c versus some combination of the two) for these sensory constructs has major implications for other areas of sensory autism research, as this decision will impact whether modality-speci c or supra-modal sensory constructs are assessed by diagnostic/phenotyping instruments, targeted by clinical interventions, correlated with other individual differences, explained with neuroscienti c or psychological models (e.g., multiple forms of sensory reactivity having a shared underlying mechanism or cause versus separate mechanisms [or even multiple mechanisms] being proposed for each form of sensory reactivity), and even incorporated into the diagnostic criteria for autism. Thus, additional research is needed to more conclusively determine whether sensory reactivity differences in autism are most appropriately studied at the level of a response pattern score (HYPER, HYPO, or SEEK) combined across modalities (e.g., 28,65,81-84), at the level of modality-speci c response pattern scores (e.g., 74,[76][77][78][79]85), or some combination of the two (e.g., interpreting both types of scores; favoring one level of analysis at different points in a study based on the research question or the speci c construct(s) being studied).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since different perceptual processes such as detection and discrimination involve distinct mechanisms, their unique associations to behavioral measures allow a better understanding of the specific biological processes that govern those relationships. Studies using psychophysics have revealed altered sensory processing in autism across multiple sensory domains (e.g., tactile, auditory, and visual), as well as different subdomains (e.g., detection and discrimination; Bonnel et al, 2010;Dwyer et al, 2022;He et al, 2021b;Heaton et al, 2008;Puts et al, 2014Puts et al, , 2017Tavassoli et al, 2011). Recent findings within the tactile domain have shown that differences in perceptual ability were related to several core traits of autism, such as social and communication differences (Bryant et al, 2019;He et al, 2021b;Ide et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to questionnaire-based measures, psychophysical approaches can provide a more objective measure of sensory processing, owing to their ability to probe lower-level perceptual function, and therefore linking to neural responding patterns (Read, 2015). Studies using psychophysics have revealed altered sensory processing in autism across multiple sensory domains (e.g., tactile, auditory, and visual), as well as different sub-domains (e.g., detection and discrimination) (Bonnel et al, 2010;Dwyer et al, 2022;Heaton et al, 2008;Puts et al, 2014Puts et al, , 2017Tavassoli et al, 2011). Recent findings from our lab and others, have found that differences in perceptual ability within the tactile domain were related to several core traits of autism, such as social and communication differences (Bryant et al, 2019;Ide et al, 2019).…”
Section: Introductionmentioning
confidence: 99%